Diagnostic accuracy of fetal choroid plexus length to head biometry ratio at 11 to 13 weeks for open spina bifida - Kalafat, E; Ting, L; Thilaganathan, B; Papageorghiou, AT; Khalil, A (Elsevier, 2020)
Background Open spina bifida is a major congenital anomaly with an estimated incidence of <1 in 1000. The diagnosis of open spina bifida is usually made during the second trimester, but first-trimester detection rate of spina bifida is increasingly reported. Recently, the mean choroid plexus length to occipitofrontal diameter ratio was reported to be increased in fetuses with open spina bifida. The ratio reflects the so-called dry brain effect caused by cerebrospinal fluid leakage and expansion of the choroid plexus into the lateral ventricles. The mean choroid plexus length to occipitofrontal diameter ratio appears to be a promising tool for early detection of open spina bifida, but its diagnostic accuracy is yet to be determined in a large cohort. Objective This study aimed to assess the predictive accuracy of mean choroid plexus length to occipitofrontal diameter ratio recorded at 11 to 13 weeks’ gestation for the detection of open spina bifida. Study Design This was a retrospective cohort of patients treated in a tertiary referral center. Fetuses in which open spina bifida was detected at 16 to 24 weeks’ gestation and normal fetuses were included in the cohort. Biparietal diameter and occipitofrontal diameter were measured in an axial view. The length of choroid plexus was measured along its longest diameter in the same plane. Ultrasound images were examined offline, and the operator was blinded to the clinical diagnosis. The predictive accuracy was evaluated using the area under the curve and positive and negative predictive values. Results We included 3300 pregnant women, of whom 24 (0.73%) had the fetuses affected by open spina bifida. The area under the curve values were 0.921 for mean choroid plexus length to occipitofrontal diameter ratio and 0.933 for its multiple of the median. Mean choroid plexus length to biparietal diameter ratio indicated similar results, with area under the curve values of 0.928 and 0.931 for raw ratio and multiple of the median ratio models, respectively. The optimal cutoffs of the mean choroid plexus to occipitofrontal diameter ratio and multiple of the median ratios were 0.662 and 1.263, respectively. The optimal mean choroid plexus to occipitofrontal diameter ratio and multiple of the median ratio cutoffs provided a positive predictive value of 90.9% and a negative predictive value of 99.6%. The number of affected spinal segments was significantly higher in fetuses with a ratio above 0.662 (P=.022). Conclusion The mean choroid plexus length to occipitofrontal diameter ratio at 11 to 13 weeks’ gestation is a promising tool for the prenatal detection of open spina bifida.